2016
DOI: 10.5935/paet.v9.n03.06
|View full text |Cite
|
Sign up to set email alerts
|

Análise do desenvolvimento de Cercospora beticola frente ao fungicida tebuconazol

Abstract: Análisis del desarrollo de cercospora beticola ante un fungicida sistemico Resumen La mancha foliar por Cercospora (Cercospora beticola) está presente prácticamente en todos los lugares donde es cultivada la betarraga (Beta vulgaris), pudiendo provocar perdida de rendimiento de azúcar de hasta un 40%, tratándose de la enfermedad más destructiva del cultivo de la betarraga, tanto como la azucarera como la de mesa. El objetivo del estudio fue evaluar el crecimiento de colonias Cercopora beticola in-vitro ante el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Although the present study is preliminary and prospective, demonstration of occurrence of the leaf spot pathogen of NZ spinach in 'seeds' deserves further investigation in Brazil and elsewhere. Pittner et al (2016), showed that C. beticola impaired beetroot seed quality, leading to loss of viability of 'seeds', and poor germination and emergence after sowing, and contributed to disseminating the pathogen over long distances. It is likely that the same applies to this fungus on NZ spinach.…”
Section: Taxonomymentioning
confidence: 99%
“…Although the present study is preliminary and prospective, demonstration of occurrence of the leaf spot pathogen of NZ spinach in 'seeds' deserves further investigation in Brazil and elsewhere. Pittner et al (2016), showed that C. beticola impaired beetroot seed quality, leading to loss of viability of 'seeds', and poor germination and emergence after sowing, and contributed to disseminating the pathogen over long distances. It is likely that the same applies to this fungus on NZ spinach.…”
Section: Taxonomymentioning
confidence: 99%
“…citrulina with slow growth, however, the mycelium coloration was white to gray. Although, it is a characteristic of the genus Cercospora, Pittner et al (2016), studying the development of Cercospora beticola reported a more accelerated mycelial growth of the colony, as in seven days the final colony diameter ranged from 30.75 to 46.50 mm. The differences in morphological and physiological characters found in the present study may be related to the conditions of the culture medium, as well as related to the natural variability of populations of the genus Cercospora.…”
Section: /9mentioning
confidence: 99%